TEXTURE VERSUS DISTANCE OF TRAVEL OF GRAVELS ON A STREAM BED: A CASE STUDY FROM FOUR STREAMS IN NW PELOPONNESE, GREECE - Kourkounis, S.; Zelilidis, A.; Panagiotakopoulou, O.; Kontopoulos, N. (Bulletin of the Geological Society of Greece, 2010)
This study concerns the change of lithology, grain size and roundness of gravels with distance downstream in lowland area from four streams which are Krathis, Kerinitis, Meganitis and Finikas. Four types of gravelly clast lithology were collected: limestone, chert, sandstone and conglomerate. In Krathis stream, the absence of variability in lithologic content is due to a short travel. The variability of the arithmetic mean depends on the width of stream channel. The roundness either remains constant or becomes better downstream because of selective transport. In Kerinitis stream, the variability or the invariability in the lithologic content is due to partly or local sample variation, partly to influx of new material, and partly to effects of increase or decrease of other types. The arithmetic mean and roundness either remain constant or are decreased downstream due to the contamination and the short travel. In Meganitis Stream, the lithologic content shows variability, the arithmetic mean absence of downstream fining gravel and the roundness variability or invariability because of the contamination and gravel mining. In Finikas Stream, the lithological content, the arithmetic mean and the roundness show either variability or invariability because of the gravel mining.